Mental health: a contrastive analysis between western and Islamic psychologies - Abdul Razak, Mohd Abbas; Abdul Razak, Abdul Latif; Mohamed Ali Zaroum, Abdulhamid (Research Management Centre, 2016)
Advancement in the way of life and urbanization has brought great many changes in the psychological well-being of people in many parts of the world. Driven by the need to be materially affluent has pushed people in the urban to unnecessary stress, anxiety, conflict, dilemma and a whole lot of other adverse psychological state of mind. Due to these psychological problems, at times, people mainly living in the cities respond in a negative way without considering the religious and ethical principles in life. In the light of this situation, this small scale research would like to explore the concept of mental health held by some selected schools in the Western mainstream psychology and Islamic psychology. It is hoped that a proper understanding on the concept of mental health and its maintenance could help people to lead a meaningful life: finding peace and harmony within themselves and in the external surrounding.